Transcatheter aortic valve‐in‐valve implantation for early failure of sutureless aortic bioprosthesis. Issue 4 (2nd April 2018) - Sun, Xiaotian; Song, Zuorui; Soffer, Daniel; Pirris, John P.
Abstract: We report a case of early failure of a Perceval sutureless aortic bioprosthesis (LivaNova, London, UK) which was treated with a transcatheter valve‐in‐valve implantation with an Edwards 3 bioprosthesis (Edwards Lifesciences, Irvine, CA).